The Onchocerciasis Control Programme in West Africa (OCP) - Boatin, B. (2012)
The Onchocerciasis Control Programme in West Africa (OCP) started operations in 1975. Its main objectives were to eliminate human onchocerciasis, as a disease of public-health importance and an obstacle to socio-economic development, from the Programme area. By the end of 2002, the OCP covered 11 West African countries, and had introduced large-scale Mectizan (ivermectin) distribution to about 10 million people, through the communitydirected treatment approach, with treatment coverages ranging from 51%-81%. Research on large-scale Mectizan use illustrated the importance of evidence-based results, the power of multicountry studies, the need for social science in community-driven endeavours and operations research, and the value of empowering communities as allies in disease control. The generous donation of Mectizan by Merck & Co., Inc., has increased general interest in health-related public-private partnerships and generated the momentum for other donations to tackle other diseases. The vector control on which the OCP was initially based successfully interrupted the transmission of the parasite causing human onchocerciasis, Onchocerca volvulus, in many areas. The introduction of Mectizan led to the decline in anterior-segment lesions in the eye and the arrest of posterior-segment lesions. The drug continues to be highly effective in morbidity control, although recently there have been reports of sub-optimal responses in some adult O. volvulus, albeit in a few, very small and isolated foci.